Emotional–Behavioral Disorders in Healthy Siblings of Children with Neurodevelopmental Disorders - Caliendo, Mariarosaria (Medicina (Kaunas), 2020)
Background and Objectives: Siblings of disabled children are more at risk of developing mental illnesses. More than 50 international studies show that about 8% of children and adolescents suffer from a mental disorder, which is almost always a source of difficulties both at the interpersonal level (in the family and with peers) and at school. Healthy siblings of children with disabilities are one of the groups most at risk for consequences in psychological health and well-being. As some authors suggest, siblings build their idea of “being people”, in terms of character and personality, by continuously and daily confronting themselves with the theme of disability and a family context subjected to continuous stress. The following contribution aims to compare emotional–behavioral disorders in healthy siblings of children with autism spectrum disorder, in healthy siblings of children with Down’s syndrome and in healthy siblings of children with typical development. Materials and Methods: The results involve 153 children from the region of Campania and their caregivers through the administration of the Strength and Difficulties Questionnaire. Results: From the data, it emerged that siblings of children with autism spectrum disorder and siblings of children with Down’s syndrome have a greater emotional fragility, especially among male subjects. Conclusions: Our results require us to reflect on the clinical and policy measures needed to ensure the well-being of siblings of disabled children, mainly through appropriate sibling coping training.